Comparative Responses of Achilles Tendinopathy to Selected Physiotherapy Approaches and the Modulating Influence of ABO Blood Group Phenotype in Nigerian Footballers: a Randomized Control Study. - Owoeye, I. O.; Aiyegbusi, A. I.; Senlaja, A. M.; Akinloye, O. (Muscles, Ligaments & Tendons Journal (MLTJ))
Background. Genetic factors have been implicated in Achilles Tendinopathy (AT) and the response to different management strategies in Caucasian populations. To account for racial differences, this study investigated the ABO blood group disposition to AT and effects on selected physiotherapy interventions in Nigerian footballers. Methods. Participants included 56 footballers made up of 28 confirmed cases of AT and 28 matched controls. Royal London Hospital test and ultrasonography were used to screen for AT. Demographic data as well as outcome variables were determined at baseline. ABO blood grouping was done by conventional serotyping. Participants with AT were randomized into three groups and managed for eight weeks using Intrasound Therapy, Therapeutic Ultrasound and Eccentric Exercises. The outcome variables of the three physiotherapy approaches in the different ABO groups were assessed and statistically analyzed using IBM SPSS 22 at the end of eight weeks. Results. Blood group O responded significantly in all outcome parameters (p < 0.05) regardless of the modality used. Blood group A had the highest OR of 3.000 (p = 0.051) while blood group B had the lowest OR of 0.625 (p = 0.758). However, all the treatment strategies were effective in the management of AT. Conclusions. The differential treatment outcomes according to ABO blood group in footballers suffering from AT may help in the development of treatment algorithms. Study registration. South African Medical Research Council (PACTR201909524416162).